METHODOLOGY FOR DEVELOPING PSYCHOLOGICAL AND PEDAGOGICAL CHARACTERISTICS OF STUDENTS IN PRIMARY SCHOOL MATHEMATICS LESSONS - Siddiqov Zayniddin Kholdorovich; Abduhoshimova Gulira’no Umidjon kizi (Bright Mind Publishing, 2025)
This article addresses the development of the psychological and pedagogical characteristics of primary school students. It discusses the significance of mathematics as a subject and highlights the aspects teachers should pay attention to when teaching mathematics in primary school.
Keywords: Primary school students, mathematics, psychological and pedagogical characteristics, ability, logic, learning process.